Expert recommendations on the assessment of wall shear stress in human coronary arteries: existing methodologies, technical considerations, and clinical applications. (30th September 2019) - Gijsen, Frank; Katagiri, Yuki; Barlis, Peter; Bourantas, Christos; Collet, Carlos; Coskun, Umit; Daemen, Joost; Dijkstra, Jouke; Edelman, Elazer; Evans, Paul; van der Heiden, Kim; Hose, Rod; et al.
Abstract: